Antifungal effect of organic acids from lactic acid bacteria on Penicillium nordicum. Issue 9 (2nd September 2018) - Guimarães, Ana; Venancio, Armando; Abrunhosa, Luís
ABSTRACT: The control of fungal contamination is particularly important to avoid both spoilage of food and feed products and the occurrence of toxic compounds, known as mycotoxins. Some lactic acid bacteria (LAB) strains have shown the capacity to inhibit fungal growth and the production of mycotoxins. In this work, cell-free supernatants (CFS) of Lactobacillus plantarum UM55 and Lactobacillus buchneri UTAD104 were tested against Penicillium nordicum radial growth and OTA production. When CFS of these strains were used, the radial growth of the fungus was inhibited by less than 20%, but the production of OTA was reduced by approx. 60%. These antifungal effects resulted from organic acids produced by LAB. The CFS of L. plantarum UM55 contained lactic acid, phenyllactic acid (PLA), hydroxyphenyllactic acid (OH-PLA) and indole lactic acid (ILA), while L. buchneri UTAD104 CFS contained acetic acid, lactic acid and PLA. These organic acids were further tested individually for their inhibitory capacity. Calculation of the inhibitory concentrations (ICs) showed that acetic acid, ILA and PLA were the most effective in inhibiting P. nordicum growth and OTA production. When the inhibitory activity of LAB cells incorporated into the culture medium was tested, L. buchneri UTAD104 inhibited the production of OTA entirely in all conditions tested, but fungal growth was only inhibited completely by the highest concentrations of cells. Acetic acid production was primarily responsible for this effect. In conclusion, the ability of LAB to inhibit mycotoxigenic fungi depends on strain capability to produce specific organic acids, and those acids may differ from strain to strain. Also, the use of LAB cells, especially from L. buchneri, in food products prone to contamination with P. nordicum (e.g. dry-cured meats and cheeses) may be an alternative solution to control fungal growth and OTA production.